The Review of Artūras Akelaitis Doctoral Thesis “Social Emotional Skills Education of Senior High School Age Students in Physical Education Lessons” (Social Sciences, Education Science 07 S) - Gudonis, Vytautas; Kaffemanienė, Irena (Pedagogika, 2017)